The Effects Of Integrating Stem Education Through Stem Module: Towards A Skilled Workforce And Consistent Learning Society - Sapora Sipon; Muhammad Zamir Othman; Norita Norwai; Roslee Ahmad; Faszly Rahim (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.